Mobile markerless augmented reality and its application in forensic medicine - Kilgus, Thomas; Heim, Eric; Haase, Sven; Prüfer, Sabine; Müller, Michael; Seitel, Alexander; Fangerau, Markus; Wiebe, Tamara; Iszatt, Justin; Schlemmer, Heinz-Peter; Hornegger, Joachim; Yen, Kathrin; et al. (International journal of computer assisted radiology and surgery, 2015)
PurposeDuring autopsy, forensic pathologists today mostly rely on visible indication, tactile perception and experience to determine the cause of death. Although computed tomography (CT) data is often available for the bodies under examination, these data are rarely used due to the lack of radiological workstations in the pathological suite. The data may prevent the forensic pathologist from damaging evidence by allowing him to associate, for example, external wounds to internal injuries. To facilitate this, we propose a new multimodal approach for intuitive visualization of forensic data and evaluate its feasibility.Methods A range camera is mounted on a tablet computer and positioned in a way such that the camera simultaneously captures depth and color information of the body. A server estimates the camera pose based on surface registration of CT and depth data to allow for augmented reality visualization of the internal anatomy directly on the tablet. Additionally, projection of color information onto the CT surface is implemented.Results We validated the system in a postmortem pilot study using fiducials attached to the skin for quantification of a mean target registration error of 4.4±1.34.4±1.34.4 ± 1.3 mm.Conclusions The system is mobile, markerless, intuitive and real-time capable with sufficient accuracy. It can support the forensic pathologist during autopsy with augmented reality and textured surfaces. Furthermore, the system enables multimodal documentation for presentation in court. Despite its preliminary prototype status, it has high potential due to its low price and simplicity.